2018
DOI: 10.1007/s10616-018-0219-3
|View full text |Cite
|
Sign up to set email alerts
|

Co-culture system of hepatocytes and endothelial cells: two in vitro approaches for enhancing liver-specific functions of hepatocytes

Abstract: Although hepatocyte transplantation and bioartificial liver support system provide new promising opportunities for those patients waiting for liver transplantation, hepatocytes are easily losing liver-specific functions by using the common in vitro cultured methods. The co-culture strategies with mimicking the in vivo microenvironment would facilitate the maintenance of liver-specific functions of hepatocytes. Considering that hepatocytes and endothelial cells (ECs) account for 80-90% of total cell populations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 24 publications
3
9
0
Order By: Relevance
“…Thus, we evaluated the effects of iEndo and 3D culture on maturation of iHep by developing a 3D w/ iEndo model in which an endothelial layer was interconnected with a hydrogel-based 3D hepatic model. Markers of hepatocyte function, such as albumin and urea secretion and CYP3A4 expression, were significantly higher into the gel in the presence of iEndo, as reported by others. , Consequently, we observed that a 3D environment and cell–cell interactions have been crucial also in our model for maintaining hepatocyte viability and function.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Thus, we evaluated the effects of iEndo and 3D culture on maturation of iHep by developing a 3D w/ iEndo model in which an endothelial layer was interconnected with a hydrogel-based 3D hepatic model. Markers of hepatocyte function, such as albumin and urea secretion and CYP3A4 expression, were significantly higher into the gel in the presence of iEndo, as reported by others. , Consequently, we observed that a 3D environment and cell–cell interactions have been crucial also in our model for maintaining hepatocyte viability and function.…”
Section: Discussionsupporting
confidence: 85%
“…iHep and iEndo were co-cultured in commercial 12-well Transwell inserts (Greiner Bio-One, 665641) having a PET membrane with a pore diameter of 0.4 μm, density of 2 × 10 6 pores/cm 2 . The iHep to iEndo cell ratio (4:1) was close to what was observed in vivo …”
Section: Methodssupporting
confidence: 86%
See 1 more Smart Citation
“…Urea levels in cocultures exhibited the opposite trend of the levels in monocultures, as there was a continuous increase in co-cultures over time ( Figure 4C). Our results are in accordance with those of a previous study (Table 1) that reported higher levels of urea and albumin secretion in hepatocytes co-cultured with endothelial cells, HSCs, and adipose cells than in a monoculture (Wang et al, 2018). Another study that examined the co-culture of HepaRG cells (cell line), LX2 cells, HUVECs, and monocytes (Table 1) also reported more urea secretion in the co-culture than in a monoculture (Rennert et al, 2015).…”
Section: Figuresupporting
confidence: 92%
“…Hepatocytes are co-cultured with an HSC line (e.g., LX2 cells), umbilical cord-mesenchymal stem cells (UC-MSCs), and umbilical cord blood (UCB)-CD34 hematopoietic stem/progenitor cells with the aim of producing a microenvironment matching the liver's in vivo microenvironment. A previous study reported the formation of a vessel-like structure in a co-culture of hepatocytes with endothelial cells and HSCs, with increased urea and albumin secretion as well as Cyp3A4 expression (Wang et al, 2018). Meanwhile, in a co-culture of MSCs and an endothelial cell line (HUVEC EA.…”
Section: Introductionmentioning
confidence: 93%